2015
DOI: 10.1007/s00266-015-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Depressor Septi Nasi Muscle Modification on Nasal Tip Rotation and Projection

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, it is shown to be the inferomedial border of the "deep pyriform space." In this study, the depressor muscle was shown to lie immediately under the nostril base [13]. However, our dissections showed a deeper muscle that lies more profound in this space.…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, it is shown to be the inferomedial border of the "deep pyriform space." In this study, the depressor muscle was shown to lie immediately under the nostril base [13]. However, our dissections showed a deeper muscle that lies more profound in this space.…”
Section: Discussionmentioning
confidence: 44%
“…These alterations are used during both cosmetic and functional rhinoplasty. Although several studies have focused on evaluating how tip modifications affect other regions of the nose along with its overall appearance, the data assessing how these maneuvers affect adjacent facial structures are more limited …”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have focused on evaluating how tip modifications affect other regions of the nose along with its overall appearance, the data assessing how these maneuvers affect adjacent facial structures are more limited. 1,2 The 2 most common techniques to increase tip projection are placement of a columellar strut and performing a tongue-in-groove maneuver. The columellar strut graft is a tai-lored piece of cartilage that is placed between the medial crura of the lower lateral cartilages and spans from the premaxilla to the nasal tip.…”
mentioning
confidence: 99%